EMA-Bench: Um Benchmark para a Avaliação de Mecanismos de Alocação Elástica de Memória - Galante, Guilherme; Andrade, Cristiane; Rodrigues, Luiz Antonio; Righi, Rodrigo da Rosa (Anais do Workshop em Clouds e Aplicações (WCGA); 2017: Anais do XV Workshop em Clouds e Aplicações, 2017)
Several works have addressed the development of mechanisms for elastic allocation of memory, creating a need for a precise way to evaluate such solutions. Analyzing the technical literature, we found a gap in the state of the art in the evaluation of vertical elasticity, since the proposals of metrics and methodologies focus on the evaluation of horizontal elasticity. In this sense, this work contributes with the development of the EMA-Bench, a benchmark for evaluating elastic memory allocation mechanisms. The benchmark enables to analyse a mecanism in terms of accuracy and time proportions spent in overprovisioning and overprovisioning states, as well as the financial costs involved. The results show that the proposed tool is able to assist the user to define the best mechanism to be adopted, ensuring cost reduction and the maintenance of quality of service. In addition, the EMA-Bench can be used by other researchers in the comparison and refinement of experiments and elastic solutions.